Osteoporosis treatment: bisphosphonates reign to continue for a few more years, at least?. Issue 1 (15th August 2016) - Pazianas, Michael; Abrahamsen, Bo
Abstract : The findings of the Women's Health Initiative study in 2002 marginalized the use of hormone replacement therapy and established bisphosphonates as the first line of treatment for osteoporosis.  Denosumab could be used in selected patients. Although bisphosphonates only maintain the structure of bone complete with any accumulated structural or material faults, their bone selectivity and effectiveness in reducing the risk of fractures, together with their low cost, have left little room for improvement for new antiresorptives. The osteoanabolic teriparatide increases new bone formation, but it is administered for up to 2 years only and the cost remains a consideration. Similar restrictions are expected to apply to an anti‐sclerostin antibody, which could be evaluated by the U.S. Food and Drug Administration in the near future. Cathepsin K–inhibiting antibody could be an alternative if approved; although an antiresorptive, it maintains bone formation, in contrast with bisphosphonates, and can be probably used for long‐term treatment.  Rare adverse effects of bisphosphonates, namely osteonecrosis of the jaws and atypical femoral fractures, have been disproportionally emphasized relative to their benefits/harm ratio. Treatment of osteoporosis is a long process, and many patients will require treatment with more than one type of drug over their lifetime.